A manganese-copper-pigment-protein complex isolated from the photosystem II of Phaeodactylum tricornutum - Holdsworth, Eric S.; Arshad, Juzu Hayati (Elsevier, 1977)
The diatom Phaeodactylum tricornutum has been grown in defined medium with known amounts of 54Mn and Cu. The diatoms were then fractionated by mild procedures to isolate a metallo-pigment-protein complex. This complex had a molecular weight of 850,000and probably was made up of 40 subunits of protein, 40 mol of chlorophyll a, 20 mol of chlorophyll c, 20mol offucoxanthin, 8 g-atoms of Cu, and between 0.6 and 2.0 g- atoms of Mn per molecule. Detergents break the complex down to small units with molecular weights of approx 25,000.The metallo-pigment-protein is probably part ofthe PSII system of chloroplasts since (i) it photoreduces dichlorophenolindophenol in the presence of diphenylcarbazide, (ii) its behavior on electrophoresis after treatment with sodium dodecylbenzene sulfonate is similar to photosystem II, (iii) its fluorescence in the presence of reducing and oxidizing agents resembles chlorophyll-protein complexes from photosystem II, and (iv) its electron paramagnetic resonance spectrum is similar to that of photosystem II in whole chloroplasts. A theory is put forward to show how this Cu- Mn-pigment-protein complex may react in the early steps of the 02-evolving system of photosystem II.